2017
DOI: 10.4067/s0717-97072017000303637
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electronic, Photophysical and Charge Transfer Properties of Small D-a Molecules Based on Thienopyrazine-Terthienyls by Changing the Donor Fragment: A DFT Study

Abstract: Four acceptor-donor organic conjugated molecules based on thieno [3,4-b]pyrazine-terthienyls were analyzed in order to explore the effect of the donor substituent on their molecular structures, electronic and optical properties. Density Functional Theory (DFT) and Time-Dependent Density Functional Theory (TD/DFT) calculations were carried out employing the B3LYP hybrid functional in combination with the 6-31G(d,p) basis set. The results suggests that the addition of electron-donating substituents to the conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This suggests that compound 1 (small ΔE) depicts an easy transition while compounds 2 and 3 (larger ΔE) are more thermodynamically stable. Although it has been reported that electron donor groups elevate the energy value of both HOMO and LUMO levels as noticeable for compound 3 with substituted isopropyl [55]. Thus, causing the reduction of ΔE as a result of the destabilization of the HOMO orbital.…”
Section: Frontier Molecular Orbital (Fmo) Analysismentioning
confidence: 93%
“…This suggests that compound 1 (small ΔE) depicts an easy transition while compounds 2 and 3 (larger ΔE) are more thermodynamically stable. Although it has been reported that electron donor groups elevate the energy value of both HOMO and LUMO levels as noticeable for compound 3 with substituted isopropyl [55]. Thus, causing the reduction of ΔE as a result of the destabilization of the HOMO orbital.…”
Section: Frontier Molecular Orbital (Fmo) Analysismentioning
confidence: 93%